1972
DOI: 10.1037/h0033373
|View full text |Cite
|
Sign up to set email alerts
|

Parental interference and romantic love: The Romeo and Juliet effect.

Abstract: The two hypotheses tested were that (a) feelings of love become more highly correlated with trust and acceptance as relationships develop through time; and (6) parental interference in a love relationship intensifies the feelings of romantic love between members of the couple. The first hypothesis was derived from our conceptualization of love and distinctions between romantic and "conjugal" love. Affirmation of this hypothesis supported a methodology for operationalizing romantic love. The second hypothesis w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

6
95
1
3

Year Published

1992
1992
2018
2018

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 177 publications
(105 citation statements)
references
References 9 publications
6
95
1
3
Order By: Relevance
“…There is some sparse evidence that feelings of love may change over the course of a relationship as folklore and stage theories suggest they do (see Cimbalo, Failing, & Mousaw, 1976;Driscoll et al, 1972;Pam, 1970). Other studies fail to support this notion.…”
Section: B Changes Over Time In Lovementioning
confidence: 99%
“…There is some sparse evidence that feelings of love may change over the course of a relationship as folklore and stage theories suggest they do (see Cimbalo, Failing, & Mousaw, 1976;Driscoll et al, 1972;Pam, 1970). Other studies fail to support this notion.…”
Section: B Changes Over Time In Lovementioning
confidence: 99%
“…In attempts to understand the inconsistent data, Sinclair, Hood, and Wright (2014) replicated Driscoll et al (1972), and found the opposite results: social interference or disapproval related to poorer relationship quality, thus supporting the social network effect. Driscoll (2014) claimed that the Romeo and Juliet effect took place in a small window in the early stages of a relationship, where trust and acceptance are only mildly associated with the magnitude of love.…”
mentioning
confidence: 87%
“…The Romeo and Juliet effect is the positive relationship between the amount of parental opposition a couple faces and the magnitude of love the couple experiences (Driscoll, Davis, & Lipetz, 1972). The Romeo and Juliet effect's namesake clearly references the relationship of Romeo and Juliet from Shakespeare: the young couple that fell deeply in love, despite their families' animosity towards each other (Shakespeare, 2017).…”
mentioning
confidence: 99%
“…Their two pronged studies noted the perceived gender difference to relationship and communication. One of the most important researches made on amorous relationship was the "Romeo and Juliet effect" [8], which covered 140 couples where parental confrontation regarding a relationship tended to solidify an amorous attraction. Indirectly, applied to education their study tested their hypothesis that:…”
Section: Introductionmentioning
confidence: 99%